2021
DOI: 10.3389/fcell.2021.641271
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 Inhibitor Induces the Apoptosis of B-Cell Acute Lymphocytic Leukemia by Inhibiting c-Myc-Mediated Glycolytic Metabolism

Abstract: B-cell acute lymphocytic leukemia (B-ALL), a common blood cancer in children, leads to high mortality. Cyclin-dependent kinase 9 inhibitor (CDK9i) effectively attenuates acute myeloid leukemia and chronic lymphoblastic leukemia by inducing apoptosis and inhibiting cell proliferation. However, the effect of CDK9i on B-ALL cells and the underlying mechanisms remain unclear. In this study, we showed that CDK9i induced the apoptosis of B-ALL cells in vitro by activating the apoptotic pathways. In addition, CDK9i r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In most cancers, CDKs openly used as vital transcriptional regulators (e.g., CDK9) for consistent production of short-lived gene products that support cell survival [ 29 ]. Therefore, CDK9 pathway dysregulation is seen in various malignancies, making it a key anticancer target [ 30 ]. This approach has been used to initiate the discovery of CDK9 inhibitors by conducting human clinical trials [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most cancers, CDKs openly used as vital transcriptional regulators (e.g., CDK9) for consistent production of short-lived gene products that support cell survival [ 29 ]. Therefore, CDK9 pathway dysregulation is seen in various malignancies, making it a key anticancer target [ 30 ]. This approach has been used to initiate the discovery of CDK9 inhibitors by conducting human clinical trials [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…\In addition to tumorigenesis, STAT3 and c-Myc play important roles in facilitating tumor cell glycolysis [ 11 , 12 ]. Therefore, we investigated the potential effect of Rh2 on the STAT3/c-Myc axis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Rg3 inhibited the Warburg effect in ovarian cancer cells and gliomas via targeting microRNA or long noncoding RNA [ 23 , 27 ]. Furthermore, it has been reported that STAT3 acts as a transcription factor to promote the expression of hexosaccharide kinase 2, which is a major glycolysis rate-limiting enzyme, resulting in glycolysis promotion [ 11 ] and c-Myc could also participate in glutamate metabolism to catalyze the decomposition of glutamine to produce lactate [ 12 ]. Thus, the STAT3/c-Myc axis plays crucial roles in glycolysis regulation.…”
Section: Discussionmentioning
confidence: 99%
“…suggested mechanism involving downregulation of MYC and the rate-limiting enzymes GLUT1, HK2, and LDHA [224,225]. In the presence of oxygen, normal cells metabolise their glucose to pyruvate, which is then completely oxidised to CO2 and H2O via the TCA cycle and oxidative phosphorylation.…”
Section: The Cellular Metabolism In Haematological Malignanciesmentioning
confidence: 99%
“…In MLL-AF9-induced murine AML, glycolysis is supported by AMP-activated protein kinase (AMPK) [ 209 ], whereas, in T-ALL, glycolysis is supported by the oncogenic NOTCH [ 210 , 211 ]. Interestingly, in B-ALL- and BCR-ABL-driven CML, inhibition of cyclin-dependent kinases (CDKs) has been shown to restrain glycolytic metabolism by a suggested mechanism involving downregulation of MYC and the rate-limiting enzymes GLUT1, HK2, and LDHA [ 224 , 225 ].…”
Section: The Cellular Metabolism In Haematological Malignanciesmentioning
confidence: 99%